In Vitro Mechanism of Action of Acanthospermum hispidum in Trypanosoma brucei - Aboagye Kwarteng Dofuor; Temitayo Samson Ademolue; Karen Nana Akua Kuampah; Frederick Ayertey; Theresa Manful Gwira (Hindawi Limited, 2022)
African trypanosomiasis is a major neglected tropical disease with significant health and economic concerns in sub-Saharan Africa. In the absence of vaccines for African trypanosomiasis, there is a consideration for alternative sources of chemotherapy. Acanthospermum hispidum DC (A. hispidum) is a herbal species of the Asteraceae family that is endowed with rich phytochemicals with unknown mechanisms of antitrypanosomal effects. This study aimed to investigate the cellular mechanisms of antitrypanosomal and antioxidant activities of A. hispidum against Trypanosoma brucei (T. brucei), a causative protozoan species of African trypanosomiasis. Fractions were prepared from the whole plant of A. hispidum through solvent partitioning by employing solvents of varying polarities (hexane, HEX; dichloromethane, DCM; ethyl acetate, EA; aqueous, AQ). The in vitro efficacies and mechanisms of antitrypanosomal activities of A. hispidum were investigated using a panel of cell biological approaches. GC-MS analysis was used to identify the major compounds with a possible contribution to the trypanocidal effects of A. hispidum. A. hispidum fractions displayed significant antitrypanosomal activities in terms of half-maximal effective concentrations (EC50) and selectivity indices (SI) (AH-HEX, EC50 = 2.4 μg/mL, SI = 35.1; AH-DCM, EC50 = 2.2 μg/mL, SI = 38.3; AH-EA, EC50 = 1.0 μg/mL, SI = 92.8; AH-AQ, EC50 = 2.0 μg/mL, SI = 43.8). Fluorescence microscopic analysis showed that at their EC50 values, the fractions of A. hispidum altered the cell morphology as well as the organization of the mitochondria, nucleus, and kinetoplast in T. brucei. At their maximum tested concentrations, the prepared fractions exhibited antioxidant absorbance intensities comparable to the reference antioxidant, Trolox, in contrast to the oxidant intensity of an animal antitrypanosomal drug, diminazene (Trolox, 0.11 A; diminazene, 0.65 A; AH-HEX, 0.20 A, AH-DCM, 0.20 A, AH-EA, 0.13 A, AH-AQ, 0.22 A). GC-MS analysis of the various fractions identified major compounds assignable to the group of alkaloids and esters or amides of aliphatic acids. The results provide useful pharmacological insights into the chemotherapeutic potential of A. hispidum toward drug discovery for African trypanosomiasis.